Pengaruh Inflasi dan GDP terhadap Tingkat Kesehatan Bank Syariah dengan Size sebagai Pembeda - Rohmah, Nisa Aulia; Darmawan, Darmawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research aims to determine the impact of Inflation and Gross Domestik Product (GDP) on the health level of Islamic Banks in Indonesia from 2014-2020 with Size as the differentiator. The population in this study is 14 Banking Companies from 2014-2020 registered with the Finansial Services Authority (OJK), and using purposive sampling technique, 14 banks were selected as the research sample. The analysis method used is panel data analysis method using Eviews 12. The health level of Islamic Commercial Bank sis calculated using the RGEC method which is measured using Non Performing Financing (NPF), Financing to Deposit Rasio (FDR), Return on Assets (ROA) and Capital Adequacy Rasio (CAR). The result of this study show that inflation and GDP do not have a significant effect on NPF, FDR and ROA. Meanwhile, inflation and GDP have a significant effect on the CAR Small Size. Keywords: Inflation, GDP, RGEC, Islamic Commercial Banks, Size